Kajian Penerapan Metode Demonstrasi Dengan Media Visual Untuk Meningkatkan Keaktifan dan Hasil Belajar Teknologi Dasar Otomotif - Dwi suhartono; subagyo subagyo; nurcholish arifin handoyono (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of the study was to determine the application of demonstration methods with visual media to increase learning activeness and learning outcomes of basic automotive technology. This study is a study using the literature study method or literature review. Data collection techniques are derived from the results of research that have been conducted and published in national and international online journals. Methods of data analysis used journal contents. The results of the preliminary study showed that learning activeness and learning outcomes of basic automotive technology were still low. Each student has differences in intellectual abilities, physical health, family backgrounds, learning habits and approaches. Efforts that can be used to overcome low activeness and learning outcomes are by using demonstration methods with the help of visual media. The application of the demonstration method encourages students' motivation to learn, enlivens learning activities, and relates theory to natural events in the environment. The application of demonstration learning methods helps students to know directly the objects used as teaching aids, making it easier for students to understand the material described by the teacher.